PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN MINYAK GORENG BIMOLI PADA PT. SALIM IVOMAS PRATAMA, Tbk LUBUK PAKAM - Ruth Felicia Angelika Pasaribu; Lidwina Agi Kakana; Tuti Elisabet Hutahuruk; Eko Andika Hutasoit (JURNAL ILMIAH SOCIO SECRETUM, 2020)
Price and promotion have very important purpose in attracting customers and it should be noticed by the company. The customer's decision will be a factor highly preferred, especially on corporate profits in the long term to help address a greater responsibility in the future. This research was conducted at PT. Salim Primary Ivomas Lubukpakam with the amount of samples taken in this study of 100 people. The research applied quantitative research methods. Simultaneously the research results showed that price and promotion had positive and significant effect on purchasing decisions (35 676> 3:35) with a significant level of 0.000> 0.05. Partially price effect had t count of 4647 and ttable value of 1.66039, the value of t> t table (4.